Household food security, anthropometric assessment of nutritional status and socioeconomic status of families in an urban community - Niño Medina, Jose Alvaro (2020)
Insufficient food production and low incomes are common problems in developing countries, thus perpetuating malnutrition and poverty conditions; establishing food security as an indicator of great impact to estimate the quality of life of families. The objective of this study was to assess the level of food security, nutritional status and socioeconomic status of families in an urban community. 155 families from an urban community of Naguanagua, Carabobo state, Venezuela were evaluated during the months August-September 2018. An ad hoc clinical history was designed, the Household Food Insecurity (FI) Scale was applied, the nutritional status was assessed by body mass index (BMI), mid-upper arm circumference (MUAC) and waist-to-height ratio (WHtR); as well as the socioeconomic status (Graffar-Méndez Castellano and the Poverty Threshold). 58.1% of families presented mild FI. 19.5% of the pediatric group presented malnutrition, while in adults, overweight and obesity stood out (44.1%); 62.5% presented cardio-metabolic risk for WHtR; 16.4% exhibited low protein reserves and 92.9% of the families were in extreme poverty. Food security was significantly correlated with BMI, WHtR, weight loss, and income. In conclusion, almost the entire sample was found in FI and in extreme poverty.